The development of industrial relations systems : some implications of Japanese experience : report prepared after a multi-national study group visit, 20th September-4th October 1975. (Paris : [Washington, D.C.] : Organisation for Economic Co-operation and Development ; [Sold by OECD], 1977)
After a brief introduction, the report discusses the pillars of the Japanese industrial relations system: 'lifetime' employment, seniority wages and enterprise unionism. It reviews the main institutions involved in industrial relations and argues the importance of the decision-making process in the Japanese enterprise and the attitudes which workers and managers bring to the enterprise.
Includes bibliographical references (pages 45-49).
Keywords: Industrial relations -- Japan; Industrial relations; Japan